Potensi Bakteri Bacillus dan Lactobacillus sebagai Probiotik Untuk Mengurangi Pencemaran Amonia pada Kandang Unggas - F. Manin; E. Hendalia; Yusrizal Yusrizal (Universitas Andalas, 2012)
The experiment was conducted in two phases. The first experiment was to observe the effectivity of six culture of Bacillus and Lactobacillus bacteria for reducing fecal ammonia. The second experiment was to evaluate the application of Bacillus and Lactobacillus bacteria as probiotic for reducing ammonia feses and litter in broiler chicken house and observe its effect on the performance. Six bacteria culture consisting of three species of Bacillus bacteria (Bacillus subtilis, Bacillus cereus and Bacillus thuringiensis) and three species of Lactobacillus bacteria (Lactobacillus acidophillus, Lactobacillus bulgaricus and Streptococcus thermophillus) were used in the first experiment and 200 Day Old Chicks CP 707 were used in application of probiotic at the second experiment. Probiotic treatment were administered by drinking water, sprayed on the litter, combination of drinking water and spraying, and without probiotic as the control. The result of the first experiment showed that the six bacterial cultures and their combination significantly (P<0, 05) reduced feses ammonia and pH. The result of the second experiment showed that the probiotic treatment was significantly (P<0, 05) reduced ammonia of fresh fecal and litter, but was not significantly improving the performance of the chickens. The conclusion of this experiment was that the combination of six bacterial cultures of Bacillus and Lactobacillus as probiotic was effective to reduce ammonia pollution in poultry house